Analysis of Clinical Symptoms of Guillain–Barré Syndrome Induced by Heat Stroke: Three Case Reports and Literature Review - Ni, Xiao-xiao; Wang, Cong-lin; Guo, Ye-qun; Liu, Zhi-feng (Frontiers in Neurology, 2022)
Background: Heat stroke is a potentially fatal condition that is caused by elevated core temperature. Guillain-Barré syndrome (GBS) induced by heat stroke is extremely rare and has only been reported in a few case reports, The purpose of this case study was to evaluate the clinical symptoms, neuroelectrophysiological and imageological features of GBS after heat stroke. Methods: We reviewed our hospital records and previously published reports to ﬁnd cases of GBS after heat stroke. The clinical, imageological and electrophysiological profiles, treatment and prognosis were presented and analyzed. Results: We retrieved 3 cases of GBS induced by heat stroke from our hospital, which presented as lesions on multiple cranial and peripheral nerves and albuminocytologic dissociation in the cerebrospinal fluid. All of these patients had disorders of consciousness at the early stage of heat stroke and a “pseudo-recovery period” after they recovered from coma after heat stroke. After immunoglobulin administration and immunoregulation therapy, these patients' neurological deficiencies were relieved significantly. But there are still disabilities and almost totally reliant on others. Conclusions: The number of the cases of GBS induced by HS reported in this study have been the most in recent 5 years. Clinicians should pay attention to heat stroke patients with sustained coma and the sudden quadriplegia. Early, exact and timely diagnosis and treatment of GBS need to be performed, to accelerate recovery and improve prognosis.